SOME RESULTS ON FIXED POINT THEOREMS IN FUZZY METRIC SPACES - GANI, A. NAGOOR; ALTHAF, M. MOHAMED (International Journal of Mathematical Archive, 2018)
This paper is an attempt to prove some critically analysed results on the fixed point theorems, which are unique and well established in fuzzy metric spaces.